2018
DOI: 10.15201/hungeobull.67.4.5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of debris flow susceptibility in El Salvador (CA): a comparison between Multivariate Adaptive Regression Splines (MARS) and Binary Logistic Regression (BLR)

Abstract: In the studies of landslide susceptibility assessment, which have been developed in recent years, statistical methods have increasingly been applied. Among all, the BLR (Binary Logistic Regression) certainly finds a more extensive application while MARS (Multivariate Adaptive Regression Splines), despite the good performance and the innovation of the strategies of analysis, only recently began to be employed as a statistical tool for predicting landslide occurrence. The purpose of this research was to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 34 publications
2
25
0
Order By: Relevance
“…In addition, its implementation usually improves the results obtained by other types of methodologies such as the logistic models [ 110 , 111 ], multiple linear regression models [ 112 ] and, in general, classical Gaussian models that assume a uniform relationship between response and predictors [ 113 ]. Likewise, Sephton [ 114 ] established that MARS is especially appropriate in the non-linear modeling of time series, while Zhang and Goh [ 100 ] showed that it is more reliable in terms of computational efficiency and interpretability than other approaches in the field of artificial intelligence such as Back Propagation Neural Network (BPNN), even outperforming the reliability of the CART models they come from [ 113 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, its implementation usually improves the results obtained by other types of methodologies such as the logistic models [ 110 , 111 ], multiple linear regression models [ 112 ] and, in general, classical Gaussian models that assume a uniform relationship between response and predictors [ 113 ]. Likewise, Sephton [ 114 ] established that MARS is especially appropriate in the non-linear modeling of time series, while Zhang and Goh [ 100 ] showed that it is more reliable in terms of computational efficiency and interpretability than other approaches in the field of artificial intelligence such as Back Propagation Neural Network (BPNN), even outperforming the reliability of the CART models they come from [ 113 ].…”
Section: Methodsmentioning
confidence: 99%
“…MARS can be focused within the new scientific paradigm [ 115 ] of the “data driven-modeling” [ 100 , 116 , 117 ], one of the foundations of machine learning techniques, being defined on a bi-objective algorithm (elaborated from a “two-stage process”) [ 118 ] in which two different phases are distinguished [ 108 , 109 , 111 , 119 , 120 ]: forward selection and backward deletion. Formally, following Koc and Bozdogan [ 102 ] and Zhang and Goh [ 100 ], its working-schema can be defined from Y , the output or objective-dependent variable response, and , a matrix of j input variables (predictors), assuming that the data are generated under an “unknown and true model”.…”
Section: Methodsmentioning
confidence: 99%
“…In this research, two scenarios were used: these scenarios were selected after altering different sample sizes and the number of replications, including 90%/10% and 80%/20% with 10 replications. To assess the robustness of the model's data sensitivity [8,22,35], 5, 10, and 15 sample data sets, (replicates) for 70%/30% sample size, were prepared through randomly multi-extracting of various data sets in the calibration and validation subsets [36]. Every set was adjusted through addition to positives (i.e., pixels having hedcut points) an equal number of randomly selected negative points, corresponding to pixels without hedcut [37].…”
Section: Gully Erosion Inventory Mappingmentioning
confidence: 99%
“…We applied five classifiers, of which RF, SVM, and MARS resulted in the best performance with >99% OAs; differences among them were only 1-5%, while OAs of PLS and KNN were even 40% worse. Although all algorithms proved their efficiency in different tasks [102,[125][126][127], we observed that accuracy depended on the similarity of the spectral characteristic of the objects and the input data. Deep learning (DL) algorithms such as artificial neural network (ANN) [128], convolutional neural network (CNN) [129], and recurrent neural network (RNN) [130] became popular and their efficiency can be higher than ML techniques.…”
Section: Discussionmentioning
confidence: 96%
“…Non-linearity is captured by knots as cutpoints. The classification works in two steps: (1) forward pass: a model is calculated involving all variables considering all possible knots; (2) backward pass: the algorithm removes the variables having the least contribution (prunes to optimal number of knots) to gain the best model using general leaving-one-out cross-validation error metrics [102,103]. We applied RKCV to obtain the optimal number of knots and degree (number of interactions) based on 30 models.…”
Section: Multiple Adaptive Regression Splinesmentioning
confidence: 99%